Circular design in the Global South - Pekka Huovila; Usha Iyer-Raniga; Christina Cheong; Riya Malhotra; Yatin Choudhary; Guillermo Penagos (Acta Polytechnica CTU Proceedings)
One Planet Sustainable Buildings and Construction Programme (SBC), led by the Ministry of the Environment, Finland and co-led by RMIT University and UN Environment Programme was initiated in 2015. Work on circular built environments commenced in the second iteration of the programme’s work plan. SBC was the first global programme that worked on circularity and responsibly sourced materials in the buildings and construction sector. In 2020, the SBC programme published a range of reports focusing on the state of play for circular built environments across specific regions, tied together with a global report. The present focus of the programme is on Africa, Asia and Latin America, where case studies are collected following a common framework. These case studies together with a global survey provide reliable performance data for responsibly sourced building materials in the Global South. The underpinning premise through this process is to support related SDGs across the social, environmental, and economic considerations and enable countries to achieve their targets under the Paris Agreement. This paper presents key findings from this study, largely derived through case studies in the Global South. The results show that not all stages of the building life cycle are addressed through local examples.